Influence of Freeze-Thaw Cycles on Engineering Properties of Tonalite: Examples from China - Su-Ran Wang; You-Liang Chen; Jing Ni; Mu-Dan Zhang; Heng Zhang (Advances in Civil Engineering)
The deterioration of the physical and mechanical properties of tonalites subjected to freeze-thaw cycling under three different temperature ranges was explored using several experimental techniques. Uniaxial compression and three-point bending tests were conducted on untreated and treated tonalite specimens. Clear decreases in uniaxial compressive strength (UCS), Young’s modulus, and fracture toughness were observed in tonalite specimens with frost damage. Although Young’s modulus and fracture toughness did not show clear decreases as the minimum temperature of the freeze-thaw cycle decreased from −30°C to −50°C, the UCS decreased almost linearly. The macromechanical characteristics of the tonalites can be explained by changes in mineral content and microstructure. The intensity of X-ray diffraction (XRD) peaks of minerals in tonalites that had not been freeze-thaw cycled were approximately 10 to 20 times higher than the peaks for the specimens subjected to freeze-thaw cycling, implying that the internal structure of tonalite is less compact after frost damage. The microstructures of the tonalite specimens were also examined using scanning electron microscopy (SEM). Increased amounts of fragmentation and breaking of structural planes were observed as the minimum temperature of the freeze-thaw cycle decreased.